Praktikalitas Media Pembelajaran Berbasis Powtoon Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Negeri 3 Palopo - Puput; Mawardi; Nur Fakhrunnisaa; Indah Safitri (Jurnal Pendidikan Terapan, 2024)
Learning media has an important role in the learning process, not only helping educators convey lessons but also providing added value in learning. Learning using media in the teaching and learning process has two important roles, namely media as a teaching aid (effectiveness) and media as a learning resource that is used by the participants themselves. One media that can be used as a solution as an interesting learning media is powtoon-based learning media. The aim of this research is to describe the practicality of the media being developed, namely powtoon-based learning media. The research carried out is research and development (R&D). The practicality data collection technique was carried out using a questionnaire to test the practicality of learning media by teachers and students. The data on the practicality test questionnaire instrument that has been filled in is then analyzed quantitatively by calculating the total score for all indicators which are then analyzed using a formula to determine the practical value. The results of the practicality carried out by the teacher obtained a score of 90% in the "very practical" category and the results of the practicality carried out by the students obtained a score of 91% in the "very practical" category. Then the average result of both obtained a score of 91% in the "very practical" category. Based on the results of practical tests carried out by teachers and students, it can be seen that the Powtoon-based learning media in Islamic religious education subjects, the Hajj and Umrah material that has been developed, is very practical to use in learning.